2012
DOI: 10.1016/j.acra.2011.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Loss of White Matter Microstructural Integrity Is Associated with Adverse Neurological Outcome in Tuberous Sclerosis Complex

Abstract: Rationale and Objectives Tuberous Sclerosis Complex (TSC) is a genetic neurocutaneous syndrome in which cognitive and social-behavioral outcomes for patients vary widely in an unpredictable manner. The cause of adverse neurological outcome remains unclear. We investigated the hypothesis that disordered white matter and abnormal neural connectivity are associated with adverse neurological outcome. Materials and Methods Structural and diffusion magnetic resonance imaging was carried out in 40 subjects with TSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 49 publications
(63 reference statements)
7
135
1
1
Order By: Relevance
“…Although there is no clear relationship between the extent and the degree of WM alterations and the clinical phenotype, there is some evidence that the more the WM is disrupted, the more severe the neurological phenotype might be [24,25,30]. Therefore, it is noteworthy to emphasize that we observed a statistically significant thinning of RNFL, even if our sample was constituted by patients who presented a relatively mild neurological phenotype.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although there is no clear relationship between the extent and the degree of WM alterations and the clinical phenotype, there is some evidence that the more the WM is disrupted, the more severe the neurological phenotype might be [24,25,30]. Therefore, it is noteworthy to emphasize that we observed a statistically significant thinning of RNFL, even if our sample was constituted by patients who presented a relatively mild neurological phenotype.…”
Section: Discussionmentioning
confidence: 61%
“…The low fractional anisotropy frequently observed in neuroimaging studies of TSC strongly supports disorganized and poorly myelinated axons, while a primary poor integrity of the axons themselves is suggested by lower axial diffusivity [22,23]. Although an axonal involvement has been hypothesized after analyzing neuroimaging data [24,25], in humans, axonal structure has never been studied in detail before. Animal models showed that there is a primary axonal developmental defect caused by the genetic mutation in the TSC genes, which leads to a secondary myelination failure [26]; the TSC/mTOR pathway appears to limit multiple axon formation and acts to confine polarized growth within a single axon in the mammalian brain, and its deregulation likely contributes to the neurological symptoms commonly observed in TSC patients [8].…”
Section: Discussionmentioning
confidence: 96%
“…This finding is significant in that other investigators have found that abnormalities in FA in normal-appearing white matter correlate with the presence and severity of cognitive impairment in TSC patients. This suggests that mTOR inhibitors may reverse microscopic structural abnormalities, resulting in improved cognition and/or seizure control, in addition to effects on cortical tubers and SEGAs [51,52]. Furthermore, no patients developed new lesions or worsening hydrocephalus or required additional surgery intervention for SEGA during the evaluation phase of the trial or during the extension study [47,49].…”
Section: Pharmacotherapymentioning
confidence: 92%
“…These studies have revealed significant associations with ASD and the TSC2 mutation, cortical tuber burden and location in the temporal lobe and cerebellum, and the age at onset, severity and type of seizures, particularly a history of infantile spasms (Bolton et al, 2002, Numis et al, 2011. Moreover, several findings implicate aberrant connectivity as a key biomarker of behavioural outcome in TSC; the number of radial migration lines (white matter abnormalities) have been found to be associated with age at seizure onset, cognitive development and autistic features, and white matter alterations and loss of structural integrity are associated with the presence of ASD (Peters et al, 2012, Lewis et al, 2013 et al, 2013b). No single clinical feature, however, is predictive of ASD outcome.…”
Section: Autism Spectrum Disorder In Tscmentioning
confidence: 99%